Evaluation of karamunting Melastoma malabathricum L leaf extract on gonad development and growth performance of tilapia Oreochromis niloticus - Samalei, Ermianus; Zairin Jr., Muhammad; Carman, Odang; Suprayudi, Muhammad Agus (Jurnal Akuakultur Indonesia, 2021)
The objective of this study was to determine the optimum dose of melastoma Melastoma malabathricum leaf extract that can inhibit the gonad development of Nile tilapia and increase its growth rate. This study used a completely randomized design containing five extract dose treatments (0, 0.5, 1, 2, and 4 g/kg diet doses) and three replications. The undifferentiated Nile tilapia larvae (7 days post hatching) were randomly distributed (n=30) to fifteen aquaria (100×50×50 cm3) and maintained for 112 days using a common recirculation system. The results showed that all dose treatments were not significantly different (P>0.05) in gonadosomatic index values of the D84 and D98 samplings. However, the 1 g/kg diet (D112) was significantly different (P